Problematyka gospodarcza w projektach Konstytucji RP - Czerwiński, Zbigniew (Wydział Prawa i Administracji UAM, 1995)
Seven drafts of the constitution submitted to the Polish Sejm by political parties have been analyzed and compared within the scope of regulations concerning the economic organization of the society: property rights, freedom of economic activity and its limitations, social security, state budget and debt, etc. Though advanced by groups of different or even (seemingly) opposite political orientations, the drafts do not differ much, all of them presenting a vision of a rather liberal state with the possibility of state intervention, in case it is necessary to protect "the public good". Most important differences may be noticed in the area of social insurance, education and health service. It is, however, often difficult to state decisively what the differences between the drafts consist in. All the drafts have been written in a very general language. It is only the future legislation which will determine the shape of the economic system of the state, and will interpret the still vague regulations of the constitution, the final version of which will certainly be a compromise between the submitted drafts.
Economic problems in the drafts of the Polish constitution